Urgensi Penguatan Hak Atas Tanah Druwe Desa di Bali - I Putu Dody Sastrawan; I Gusti Nyoman Guntur; Dwi Wulan Titik Andari (Sekolah Tinggi Pertanahan Nasional, 2018)
Abstract: Druwe Desa land is a customary whose management is implemented and belongs to desa pakraman. Although it has been acknowledged juridically, but the existence of Druwe Desa land in Bali is experiencing a vacuum related to the legal subject. On that basis, desa pakraman is appointed as subject of rights with respect to its land through the Decree of the Minister of Agrarian Affairs and Spatial/Head of National Land Agency Number 276/Kep-19.2/X/2017. The purpose of this research is to: (1) Make map of distribution of Druwe Desa land; (2) Describe the importance of strengthening the right to Druwe Desa land; (3) Describe the procedures for strengthening the right to Druwe Desa land; (4) Describe the benefits of the strengthening of Druwe Desa land rights. To achieve these objectives, qualitative research methods with ethnographic approach are used to understand the efforts of the community in maintaining the existence of Druwe Desa land. The results of this study indicate the potential shifting of the status of Druwe Desa land ownership that can indirectly threaten its existence. For that reason, it is necessary to strengthen the right to Druwe Desa land so that there will be no problems that can reduce the existence of asset of desa pakraman. Steps that need to be taken is the process of certification to obtain legal certainty.Keywords: Druwe Desa land, desa pakraman, Existence, Tri Hita Karana, Awig-Awig Intisari: Tanah Druwe Desa merupakan tanah adat yang pengelolaannya dilaksanakan dan menjadi milik desa pakraman. Meskipun sudah diakui secara yuridis, namun keberadaan tanah Druwe Desa di Bali mengalami kekosongan terkait subjek hukumnya. Atas dasar itulah, desa pakraman ditunjuk sebagai subjek hak berkenaan dengan tanah miliknya melalui Keputusan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 276/Kep-19.2/X/2017. Tujuan penelitian ini adalah untuk: (1) Membuat peta sebaran tanah Druwe Desa; (2) Mendeskripsikan pentingnya penguatan hak atas tanah Druwe Desa; (3) Mendeskripsikan tata cara penguatan hak atas tanah Druwe Desa; (4) Mendeskripsikan manfaat hasil penguatan hak atas tanah Druwe Desa. Untuk mencapai tujuan tersebut, digunakan metode penelitian kualitatif dengan pendekatan etnografi guna memahami upaya masyarakat dalam menjaga eksistensi tanah Druwe Desa. Hasil dari penelitian ini menunjukkan adanya potensi pergeseran status kepemilikan tanah Druwe Desa yang secara tidak langsung dapat mengancam eksistensinya. Untuk itu perlu dilakukan penguatan hak atas tanah Druwe Desa agar tidak terjadi permasalahan yang dapat mengurangi keberadaan aset desa pakraman tersebut. Langkah yang perlu diambil adalah proses pensertipikatan untuk mendapatkan kepastian hukum.Kata Kunci: Tanah Druwe Desa, desa pakraman, Eksistensi, Tri Hita Karana, Awig-Awig Pendah